Three Approaches to Writing School Programs with Official Language Minorities : Research Brief no. 9 - Gani, Raphaël (Quebec English-speaking Communities Research Network (QUESCREN), 2023)
Keywords: Official Language Minority Community (OLMC)

Trois approches pour rédiger des programmes scolaires avec les minorités de langue officielle : Résumé de recherche no. 9 - Gani, Raphaël (Quebec English-speaking Communities Research Network (QUESCREN), 2023)
Keywords: Official Language Minority Community (OLMC)

Resolution 2023-03 : Better Develop the New Culture and Citizenship in Québec Program - Quebec Federation of Home and School Associations (QFHSA) (2023)

Resolution 2023-04 : Maintain Sexuality Education as a Separate Program - Quebec Federation of Home and School Associations (QFHSA) (2023)

Résolution 2022–02 : Demande de garder la race, la religion et la culture comme thèmes centraux au cours proposé sur la citoyenneté - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-02 : Request to Maintain Race, Religion, and Culture as Central Themes in the Proposed Citizenship Course - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-07 : Quebec English CEGEP Curricula - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2021-04 : Request to Revise and Improve the Secondary III and Secondary IV History of Quebec and Canada Curriculum - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-06 : Curriculum Development - Quebec Federation of Home and School Associations (QFHSA) (2021)

Représentation des anglophones à l'emploi dans les ministères de l'éducation du Québec et dans l'élaboration des programmes d'études - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Les anglophones sont depuis longtemps sous-représentés dans le secteur de la fonction publique du Québec (Cooper, Donovan et O’Donnell, 2019). En 2019, 506 des 53 570 employés réguliers (0,9 %) de la fonction publique au Québec étaient des anglophones, soit environ un dixième de leur proportion dans la population totale de la province. (Secrétariat du Conseil du trésor, 2019; Statistique Canada, 2017).
Keywords: Official Language Minority Community (OLMC)

Representation of English-speakers in Quebec's Education Ministries and Curriculum Development - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
There is a longstanding underrepresentation of English speakers in Quebec’s public sector (Cooper, Donovan, & O’Donnell, 2019). In 2019, 506 out of 53,570 regular employees (0.9%) in Quebec’s public service were Anglophones, roughly one tenth of their proportion in the total population of the province (Secrétariat du Conseil du trésor, 2019; Statistics Canada, 2017).
Keywords: Official Language Minority Community (OLMC)

Les écoles anglophones en transition : Établir un leadership pédagogique partagé - Advisory Board on English Education (2020)

Réponse à la consultation sur le programme Éthique et culture religieuse - Advisory Board on English Education (2020)
La Commission de l’éducation en langue anglaise (CELA) a pour mandat de « donner des avis au ministre de l’Éducation et de l’Enseignement supérieur sur toutes les questions touchant les services éducatifs dans les écoles anglophones primaires et secondaires ainsi que dans les centres d’éducation aux adultes et de formation professionnelle ». Elle est donc tenue de soumettre le présent mémoire dans le cadre de la consultation sur le remplacement du programme Éthique et culture religieuse (ECR). Cependant, nous, les membres, trouvons frustrant le court délai accordé pour la consultation, car nous n’avons pas le temps d’examiner minutieusement les études pertinentes, ni de consulter le milieu pour bien comprendre comment le cours est donné et accueilli dans les écoles. Les décisions relatives au curriculum, comme celles d’ordre pédagogique, devraient s’appuyer sur les conclusions d’études fiables. Nous avons des doutes quant à l’utilité des questions du sondage en ligne. Si l’on avait demandé aux répondants d’évaluer leur connaissance du contenu et de la pédagogie du programme actuel d’ECR, l’information aurait pu aider à jauger la pertinence de leurs opinions. Bien que le programme d’ECR représente une petite partie du programme global de formation au primaire et au secondaire, il joue un rôle déterminant dans le développement de nos futurs citoyens et mérite une réflexion approfondie. Cela dit, nous espérons que le ministre étudiera attentivement les documents qui lui seront soumis et que le programme proposé n’est pas déjà un fait accompli. Dans les huit thèmes du programme proposé, l’étude des différentes religions n’est mentionnée qu’une seule fois, ce qui traduit clairement l’intention du gouvernement de promouvoir la laïcisation de la vie publique. Nous doutons, cependant, que cela contribue à former efficacement les citoyens de demain dans une société de plus en plus diversifiée et pluraliste. Vu le temps dont nous disposons, nous ne pouvons que soulever la question. Il y a toutefois des problèmes pratiques et pédagogiques qui, selon nous, doivent être considérés et dont nous traiterons plus en détail ci-dessous.

Response to the Consultation on the Proposed Ethics and Religious Culture Program - Advisory Board on English Education (2020)
The mandate of the Advisory Board on English Education (ABEE) is “to advise the Minister of Education and Higher Education on all matters affecting the educational services offered in English elementary and secondary schools and adult and vocational education centres.” For this reason, we are obliged to offer this contribution to the consultation on replacing the Ethics and Religious Culture (ERC) program, although we are frustrated that the short time allowed for consultation does not allow us to do a careful study of pertinent research and to consult with the milieu to have a fuller understanding of how this course is offered and received in the schools. Curriculum decisions, just as pedagogical decisions, should be based on conclusions from robust research. We question the value of the questions in the on-line survey: it might have been revelatory to have asked respondents to estimate their knowledge of the content and pedagogy of the existing ERC program to assess the pertinence of their opinions. Although the program occupies a small part of the overall elementary and secondary school curriculum, it is a critical program in the development of our future citizens and one that merits thoughtful consideration. Nevertheless, we also hope that the Minister will consider carefully the submissions made to him and that the proposal does not represent a fait accompli. It is clear that the relegation of the study of different religions to one reference in the eight themes of the proposed program represents the government’s intent to further the secularization of public life. However, we question whether this will effectively educate future citizens in an increasingly diverse and multi-faceted society. In the time available, we can only raise the question, but there are pedagogical and practical issues that we believe need to be considered and that we will elaborate.

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook - Eastern Townships Resource Centre (ETRC) (2019)

An Independent Report of the History Experts Committee On the Provincial History of Québec and Canada Program and Approved English Textbooks - Commission scolaire English-Montreal / English Montreal School Board (2018)
In September 2017, the Ministry of Education implemented a revised Secondary III and IV compulsory History of Québec and Canada program. This program raised a number of issues that became of concern to the English Montreal School Board (EMSB). Given these concerns, the EMSB commissioned an independent History Experts Committee to review the content of this program as well as the Ministry-approved English-language textbooks. The following is a summary of the findings of this Committee

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)

Réponse au document de consultation sur la création d’un institut national d’excellence en éducation - Advisory Board on English Education (2017)

Resolution 2017-04 : Quebec Secondary III and IV History Curriculum: In Need of Change - Quebec Federation of Home and School Associations (QFHSA) (2017)

Software Coding : Resolution 2017-05 - Quebec Federation of Home and School Associations (QFHSA) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

Quebec's Secondary III & IV History Curriculum : In Need of Change - Quebec Federation of Home and School Associations (QFHSA) (2016)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Briefs Submitted to the Minister of Education, Recreation and Sports : 2011 - Advisory Board on English Education (2011)

English Schools in Transition : Building Collaborative Leadership - Advisory Board on English Education (2000)

AQ Congratulates the Quebec Liberal Party Youth Wing for its Recommendation to Start Teaching English as a Second Language in Grade 1 instead of Grade 4 - Alliance Quebec (AQ) (2000)

Culture and English Schools in Play - Advisory Board on English Education (1999)
In this 1999 report to the Minister of Education, the Advisory Board on English Education examines Québec Schools on Course, the educational policy statement published by the Ministère de l’Éducation du Québec (MEQ) which calls for improvement of the cultural content of the curriculum.

La mise en jeu de la culture et l'école de langue anglaise - Advisory Board on English Education (1999)
Dans le présent rapport, la Commission de l’éducation en langue anglaise (CELA) étudie l’énoncé de politique du Ministère, intitulé L’école, tout un programme, qui appelle à l’amélioration du contenu culturel des programmes afin de favoriser la réussite scolaire.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1996)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1995)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1994)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1985)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1984)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1983)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1982)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1982)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1981)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1981)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1980)

Final Report on the Aspirations and Expectations of the Quebec Black Community with Regard to Education - The Black Community Work Group on Education (1978)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1977)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1967)

Report of Sex Education Committee - Quebec Federation of Protestant Home & School Associations (1967)
The term "sex education" as used in the terms of reference has been interpreted by the committee to mean education in which sexual, biological and physiological facts are only disclosed in the full context of human relations. It must be made clear at the outset therefore, that sex education, in our opinion, cannot consist of less than education in Human Relations in which sexual growth is seen as part of the whole growth of the individual and in which basic sexual facts are discussed in the context of the growing boy and girl in their development into manhood and womanhood.